Nitric oxide (NO) level of the follicular fluid in endometriosis patients - Cahyono Hadi; Djaswadi Dasuki; Ahmad Hamim Sadewa; Indwiani Astuti; Awal Prasetyo (Universitas Airlangga, 2018)
Objectives: To ascertain the nitric oxide (NO) level of the follicular fluid of endometriosis sufferers compared with that of the non-endometriosis patients.Materials and Methods: Follicular fluid was taken from 64 women, but only 54 continued with further laboratory test. Women with endometriosis had their follicular fluid taken during laparoscopy, while the follicular fluid from non-endometriosis women was taken during tubectomy. Nitric Oxide level was analyzed using the PCR-RFLP method. Data were analyzed using software STATA Intercooled Version 11.Results: NO level in endometriosis is higher than that in non-endometriosis and has a significant relationship with all the variables (age, parity, dysmenorrhea, dyspareunia, types of endometriosis, and grade of endometriosis).Conclusion: The NO level in endometriosis is higher than that in non-endometriosis. The distribution of the polymorphism of allele GG is greater than that in non-endometriosis. The existence of polymorphism GG caused a higher eNOS, increasing NO level, causing a decrease in fertility which derived from the degenera-tive oocyte.